2002
DOI: 10.1152/japplphysiol.01065.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatine supplementation on oxygen uptake kinetics during submaximal cycle exercise

Abstract: The purpose of this study was to test the effect of oral creatine (Cr) supplementation on pulmonary oxygen uptake (VO(2)) kinetics during moderate [below ventilatory threshold (VT)] and heavy (above VT) submaximal cycle exercise. Nine subjects (7 men; means +/- SD: age 28 +/- 3 yr, body mass 73.2 +/- 5.6 kg, maximal VO(2) 46.4 +/- 8.0 ml. kg(-1). min(-1)) volunteered to participate in this study. Subjects performed transitions of 6-min duration from unloaded cycling to moderate (80% VT; 8-12 repeats) and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
4
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 43 publications
5
41
4
1
Order By: Relevance
“…Interestingly, however, the value was increased by ϳ10 and ϳ4% for moderate-intensity and heavy-intensity exercise, respectively. It is possible that intersubject variability in the changes to muscle Cr content in response to dietary Cr supplementation (8,12), which was not directly assessed by Jones et al (28), precluded the attainment of statistical significance. In the same study, steady-state V O 2 was not different following Cr loading for moderate-intensity exercise, consistent with the similar change in [PCr] observed in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, however, the value was increased by ϳ10 and ϳ4% for moderate-intensity and heavy-intensity exercise, respectively. It is possible that intersubject variability in the changes to muscle Cr content in response to dietary Cr supplementation (8,12), which was not directly assessed by Jones et al (28), precluded the attainment of statistical significance. In the same study, steady-state V O 2 was not different following Cr loading for moderate-intensity exercise, consistent with the similar change in [PCr] observed in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…According to Meyer's electrical analog model, a greater muscle total Cr content consequent to dietary Cr "loading" would be expected to result in slower muscle [PCr] and V O 2 kinetics. In the only study to date on this topic, Jones et al (28) were unable to detect a significant change in the phase II pulmonary V O 2 kinetics following Cr loading at either moderate (i.e., below the estimated lactate threshold, LT) or heavy (i.e., ϾLT) intensities of cycle ergometer exercise. However, pulmonary V O 2 kinetics can only provide an indirect estimate of muscle [PCr] or V O 2 kinetics (4,18,56), and it is possible that such measurements were not sufficiently sensitive to detect changes in the dynamics of muscle oxidative metabolism following Cr loading.…”
mentioning
confidence: 96%
“…It has been repeatedly demonstrated that the muscle and pulmonary V O 2 responses during heavy and very heavy intensity exercise manifest an additional excess component supplementing the underlying fundamental exponential response kinetics (e.g., Refs. 7,8,14,16,17,19,27,28,37,40). While many mechanisms for this V O 2 slow component have been suggested (30), the most commonly proposed view is that of ongoing muscle recruitment during the slow component phase, presumably mediated through ongoing muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of ATP/ADP and PCr/Cr are linked in the mitochondria to the creatine kinase (CK) reaction (Chance and Williams 1955;Meyer et al 1984;Mahler 1985;Balaban 1990). An increase in the total creatine pool [PCr + Cr] through Cr loading has been shown to influence the O 2 on-kinetics (Jones et al 2002;Jones et al 2009). In particular, Jones et al (2002) There has been a limited focus of the Cr literature on endurance exercise performance given the purported primary mechanism of action of Cr is to enhance the capacity for PCr resynthesis during recovery from repeated bouts of intense exercise.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%
“…An increase in the total creatine pool [PCr + Cr] through Cr loading has been shown to influence the O 2 on-kinetics (Jones et al 2002;Jones et al 2009). In particular, Jones et al (2002) There has been a limited focus of the Cr literature on endurance exercise performance given the purported primary mechanism of action of Cr is to enhance the capacity for PCr resynthesis during recovery from repeated bouts of intense exercise. In one of the first studies to investigate the effects of 21g Cr monohydrate + 21g dextrose for 5 days during intense endurance exercise lasting approximately 1 hour, no effect on performance 8 was reported although the accumulation of inosine monophosphate (IMP, a marker of muscle energy balance) at the end of the performance ride was significantly lower on the Cr trial.…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%